A New and Practical Oral Contraceptive Agent: Norethindrone with Mestranol - Dickinson, J. H. (1963)
The usefulness of a new oral contraceptive compound containing norethindrone 5 mg. and mestranol 0.075 mg. (Ortho-Novum) was studied. One hundred and seventeen private patients used this preparation for a total of 998 menstrual cycles. There were no pregnancies. Side effects were minimal and caused few (11 patients) to discontinue use. The most significant of these was weight gain and a premenstrual tension syndrome including nausea, breakthrough bleeding and skin effects. Other symptoms were minor and easily controlled. Instruction in use of the preparation is easy. Patient acceptance is excellent. Possible masculinizing effects, liver damage, or harmful effects on the uterus were checked specifically by laboratory evaluation; no significant abnormal findings were noted. This appears to be an effective oral contraceptive which is well accepted by the patient and which produced no serious side effects as used in this study.